Pharmacodynamic profiling of commonly prescribed antimicrobial drugs against Escherichia coli isolates from urinary tract - Cuba, Gabriel Trova [UNIFESP] (2014)
Since antimicrobial resistance among uropathogens against current first line agents has affected the management of severe urinary tract infection, we determined the likelihood that antibiotic regimens achieve bactericidal pharmacodynamic exposures using Monte Carlo simulation for five antimicrobials (ciprofloxacin, ceftriaxone, piperacillin/tazobactam, ertapenem, and meropenem) commonly prescribed as initial empirical treatment of inpatients with severe community acquired urinary tract infections. Minimum inhibitory concentration determination by Etest was performed for 205 Brazilian community urinary tract infection Escherichia coli strains from 2008 to 2012 and 74 E. coli bloodstream strains recovered from a surveillance study. Pharmacodynamic exposure was modeled via a 5000 subject Monte Carlo simulation. All isolates were susceptible to ertapenem and meropenem. Piperacillin/tazobactam, ceftriaxone and ciprofloxacin showed 100%, 97.5% and 83.3% susceptibility among outpatient isolates and 98.6%, 75.7% and 64.3% among inpatient isolates, respectively. Against outpatient isolates, all drugs except ciprofloxacin (82.7% in aggressive and 77.6% in conservative scenarios) achieved high cumulative fraction of response: car-bapenems and piperacillin/tazobactam cumulative fraction of responses were close to 100%, and ceftriaxone cumulative fraction of response was 97.5%. Similar results were observed against inpatients isolates for carbapenems (100%) and piperacillin/tazobactam (98.4%), whereas ceftriaxone achieved only 76.9% bactericidal cumulative fraction of response and ciprofloxacin 61.9% (aggressive scenario) and 56.7% (conservative scenario) respectively. Based on this model, standard doses of beta-lactams were predicted to deliver sufficient pharmacodynamic exposure for outpatients. However, ceftriaxone should be avoided for inpatients and ciprofloxacin empirical prescription should be avoided in both inpatients and outpatients with complicated urinary tract infection.